Company visits as an opportunity for entrepreneurial learning. (2017) - Sommarström, Kaarina; Ruskovaara, Elena; Pihkala, Timo
The research field of entrepreneurship education has emerged rapidly. However, there is a lack of knowledge regarding the organisation of company visits. Especially, the utilisation of companies to expand the learning environment has been largely dismissed. This study examines company visits as an opportunity for entrepreneurial learning in compulsory education. The empirical part of this study considers five cases. The informants are teachers in compulsory education. The findings show that company visits are a broader concept than previous literature suggests, and depending on the way the visits are organised, they create very different learning possibilities. The cases indicate that teachers willingly cooperate with companies, although organising company visits remains a challenge. The findings highlight the positive effects of school-company cooperation, and especially the cases where students implement the process to create significant potential for entrepreneurial learning.